VD_FINDINFO HC / 2014 / 998 vom 22. Dezember 2014 - VD Tribunal cantonal (2014)
RENVOIDROIT DES ÉTRANGERS, DÉTENTION AUX FINS D'EXPULSION | 75 al. 1 let. g LEtr, 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr